Internal Model Control for Rudder Roll Stabilisation and Course Keeping of a Surface Marine Craft⁎. Issue 29 (2018) - Kazantzidou, Christina; Perez, Tristan; Donaire, Alejandro; Valentinis, Francis
Abstract: This paper presents a novel control design procedure for simultaneous course keeping and rudder roll stabilisation for a surface marine craft. We address the design using the Internal Model Principle. This approach has been used to analyse fundamental limitations of rudder roll stabilisation due to unstable zero dynamics, but it has not been exploited for full control system design. The design is based on roll sensitivity shaping and uses a simplified parametric model of the roll-induced wave motion. This design provides opportunities for adapting the performance due to changes in environmental and sailing conditions. This is a need driven by a well-known issue leading to performance degradation in this control problem, which is due to the presence of unstable zero dynamics and significant changes in the power spectrum of the disturbance.